Meprin A and meprin α generate biologically functional IL-1β from pro-IL-1β - Herzog, Christian (2009)
The present study demonstrates that the oligomeric metalloendopeptidase meprin A purified from kidney cortex and recombinant meprin α are capable of generating biologically active IL-1β from its precursor pro-IL-1β. Amino-acid sequencing analysis reveals that meprin A and meprin α cleave pro-IL-1β at the His(115)-Asp(116) bond, which is one amino acid N-terminal to the caspase-1 cleavage site and five amino acids C-terminal to the meprin β site. The biological activity of the pro-IL-1β cleaved product produced by meprin A, determined by proliferative response of helper T-cells, was 3-fold higher to that of the IL-1β product produced by meprin β or caspase-1. In a mouse model of sepsis induced by cecal ligation puncture that results in elevated levels of serum IL-1β, meprin inhibitor actinonin significantly reduces levels of serum IL-1β. Meprin A and meprin α may therefore play a critical role in the production of active IL-1β during inflammation and tissue injury.